REKAYASA MESIN PEMARUT SINGKONG DENGAN SISTEM ROOL BEAM SEBAGAI UPAYA PENINGKATAN PRODUKSI KARAK ROMEO DIKABUPATEN SUKOHARJO - Suhartoyo - ('Ibadatuna : Jurnal Pengabdian Masyarakat, 2024)
Romeo food is one of the snacks made from grated cassava which is then processed to become karak romeo. The center for making Romeo food is in Laban village, Sukoharjo district. The partners of this community service activity are UKM makers of romeo food in Laban village, Sukoharjo. The condition of the partners has not been optimal because the work is still manual, and it is a problem because the number of workers is very limited if they want to increase the amount of production. With a touch of technology through the community service program, it is very helpful in production results. The community service activities carried out include making graters, machine operation training, machine maintenance training, production management training, and product packaging training. The results of community service through the community service program that has been implemented are that there is an increase in the production process, especially romeo food, which used to be manual production using cassava ingredients, only able to produce cassava ingredients of approximately 20 kg per production per day by using machines from the community service team, production can increase to reach 45 kg-60 kg depending on the existing orders. This means that the use of machines made by the service team can increase production results with the same workforce. Increased production means that it can also produce increased profits.